Maternal determinants of low birth weight in a rural block of Haryana: a community based study - Verma, Ramesh; Kumar, Manoj; Bhalla, Kapil; Kumar, Raj; Dhaka, Rohit; Chayal, Vinod (International Journal Of Community Medicine And Public Health, 2017)
Background: If a pregnant woman is taken care of as advised, she will give birth to a child who does not have any diseases- a healthy, physically strong, radiant and well-nourished baby. Low-birth-weight (LBW) is universally used as an indicator of health status and is an important subject of national concern and a focus of health policy. In 2013, more than 20 million newborns, an estimated 16% of all babies born globally that year, had LBW. DLHS-4 (2012-2013) Haryana reported the prevalence of LBW as 13.6% in rural area (below 2.5 kg). The aim of study was to identify the maternal determinants of low birth weight in a rural block of Haryana. Methods: The CHC Dighal (Jhajjar) has 20 sub-centers, out of these sub-centers, 10 sub-centers were selected by simple random sampling. The 800 study subjects were enrolled over a period of one year (June 2015 to May 2016). Results: In present study, 136 (17%) newborn had low birth weight. The odds of LBW delivered were 1.76 times higher for female babies as compared to male babies. Mothers who were educated up to primary level had 3.768 times higher odds. Conclusions: The study conclude that sex of baby, caste, type of family, socioeconomic status identified as independent predictor of LBW. Health functionaries should focus on preventing incidence of preterm deliveries, anemia, diabetes etc.